(untitled) (MAUSAM, 1986)
A three level P.E. model is integrated for 5 days to study the evolution of the low level westerly flow with the forcing provided by an idealized terrain of Peninsular India, Burma and Tibetan area (maximum height restricted to 1 km) in the lowest layer of the model atmosphere. The first experiment is conducted with a simple mode of uniform westerly flow throughout atmosphere without any shear. The model results are compared with the analytical solutions of the linear steady state vorticity equation. The results obtained from both the methods showed formation of the lee-troughs on the eastern side of the Peninsular India and Burma mountains respectively. The second experiment is conducted with idealized wind profile having both horizontal and vertical shears. The experiment is conducted to assess the effect of upper tropospheric easterlies on the low level circulation. The results of the experiments are presented. However, there are other types of forcings also influencing the monsoon flow, there is need for investigating them separately.